Design selection and dynamic response analysis of CFG pile composite foundation in soft soil areas - Zhang, Huahua; Liu, Liming; Feng, Wei; Zhou, Yuru; Zheng, Wei; Zhao, Bingqin (Frontiers in Materials, 2022)
The construction of roads along rivers plays a crucial role in the construction of economic belts and social and economic development along rivers. Roadbeds are the foundation of highway construction, while the soft soil foundation is widely distributed on both sides of rivers, resulting in some difficulties for roadbed construction and highway use. Despite diverse technical methods for the treatment of general roadbeds, the treatment of soft soil roadbeds should be further explored. In this paper, various advantages of applying CFG (Cement Fly-ash Gravels) pile treatment to the soft foundation in Bailinhe Road, Yichang are investigated. Specifically, the soft soil roadbed treated by CFG pile is numerically simulated, the changes in engineering index response before and after foundation treatment are analyzed, and then the dynamic analysis under vehicle dynamic load is performed. The results demonstrate that the reinforcement effect of the CFG pile significantly weakens the influence of vehicle dynamic load on roadbeds.